Temporal Variations in Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Infections by Race and Ethnicity in Arkansas. (23rd March 2022) - Kennedy, Joshua L; Forrest, J Craig; Young, Sean G; Amick, Benjamin; Williams, Mark; James, Laura; Snowden, Jessica; Cardenas, Victor M; Boothe, Danielle; Kirkpatrick, Catherine; Modi, Zeel; Caid, Katherine; et al.
Abstract: Background: The aim of this study was to estimate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection rates in the small rural state of Arkansas, using SARS-CoV-2 antibody prevalence as an indicator of infection. Methods: We collected residual serum samples from adult outpatients seen at hospitals or clinics in Arkansas for non–coronavirus disease 2019 (COVID-19)–related reasons. A total of 5804 samples were identified over 3 time periods: 15 August–5 September 2020 (time period 1), 12 September–24 October 2020 (time period 2), and 7 November–19 December 2020 (time period 3). Results: The age-, sex-, race-, and ethnicity-standardized SARS-CoV-2 seroprevalence during each period, from 2.6% in time period 1 to 4.1% in time period 2 and 7.4% in time period 3. No statistically significant difference in seroprevalence was found based on age, sex, or residence (urban vs rural). However, we found higher seroprevalence rates in each time period for Hispanics (17.6%, 20.6%, and 23.4%, respectively) and non-Hispanic Blacks (4.8%, 5.4%, and 8.9%, respectively) relative to non-Hispanic Whites (1.1%, 2.6%, and 5.5%, respectively). Conclusions: Our data imply that the number of Arkansas residents infected with SARS-CoV-2 rose steadily from 2.6% in August to 7.4% in December 2020. There was no statistical difference in seroprevalence between rural and urban locales. Hispanics and Blacks had higher rates of SARS-CoV-2 antibodies than Whites, indicating that SARS-CoV-2 spread disproportionately in racial and ethnic minorities during the first year of the COVID-19 pandemic. Abstract : In this prospective convenience sampling of remnant sera, we found increasing SARS-CoV-2 seroprevalence from 2.6% to 7.4% during August–December 2020. Higher seroprevalence rates were found in Hispanics and Blacks compared to Whites across all time periods.